Chemically delaminated free standing covalent organic nanosheets (CONs) - Khayum, Abdul M.; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; porous polymers; ultra thin nano sheets

Chemically stable urea based COF for size selective heterogeneous catalysis - Basu, Arghya; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: chemical stability; Covalent organic framework; heterogeneous catalysis

Covalent organic framework thin-films for molecular separation - Dey, Kaushik; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Separation; Thin-films

Crystalline porous materials for gas adsorption - Pal, Tapan Kumar; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; gas adsorption

Decoding the morphological diversity in two dimensional crystalline porous polymers - Halder, Arjun; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Density functional calculations; Morphology

Supramolecular reassembly of self-exfoliated ionic covalent organic nanosheets for label-free detection of double-stranded DNA - Mal, Arindam; Mishra, Rakesh K.; Praveen, Vakayil K.; Khayum, M. Abdul; Banerjee, Rahul; Ajayaghosh, Ayyappanpillai (Angewandte Chemie-International Edition, 2018)
Ionic covalent organic nanosheets (iCONs), a member of the two-dimensional (2D) nanomaterials family, offer a unique functional platform for a wide range of applications. Herein, we explore the potential of an ethidium bromide (EB)-based covalent organic framework (EB-TFP) that self-exfoliates in water resulting in 2D ionic covalent organic nanosheets (EB-TFP-iCONs) for the selective detection of double-stranded DNA (dsDNA). In an aqueous medium, the self-exfoliated EB-TFP-iCONs reassemble in the presence of dsDNA resulting in hybrid EB-TFP-iCONs-DNA crystalline nanosheets with enhanced fluorescence at 600 nm. Detailed steady-state and time-resolved emission studies revealed that the reassembly phenomenon was highly selective for dsDNA when compared to single-stranded DNA (ssDNA), which allowed us to use the EB-TFP-iCONs as a 2D fluorescent platform for the label-free detection of complementary DNA strands.
Keywords: Covalent organic framework; DNA; ionic assembly; ionic covalent organic nanosheets; label-free detection

Transforming covalent organic framework into thin-film composite membranes for hydrocarbon recovery - Biswal, Bishnu P. (Separation Science and Technology, 2018)
We, for the first time, employed chemically stable covalent organic framework (COF) (TpPa-1) as a transport-active phase within the polymer (styrene-butadiene rubber; SBR) matrix to make TpPa-1@SBR thin-film composite (TFC) membranes. Three composite membranes, viz., TpPa-1(30)@SBR, TpPa-1(50)@SBR, and TpPa-1(70)@SBR have been prepared with varying COF content. These membranes were characterized for gas permeance and results were compared with the pristine SBR-based TFC membrane. The fully organic nature of chemically stable COF offered good compatibility with the host polymer matrix (SBR) and resulted into flexible TFC membranes even at 70% of COF loading; compared to the other porous material (MOFs or Inorganic fillers), it is appreciable.
Keywords: Covalent organic framework; hydrocarbon recovery; propylene–propane; styrene-butadiene rubber; thin film composite